2021
DOI: 10.3390/horticulturae7100335
|View full text |Cite
|
Sign up to set email alerts
|

Intercropping Vicia sativa L. Improves the Moisture, Microbial Community, Enzyme Activity and Nutrient in Rhizosphere Soils of Young Kiwifruit Plants and Enhances Plant Growth

Abstract: Drought, low nutrition, and weeds have become the major limiting factors of young kiwifruit orchards. In this study, the effects of intercropping Vicia sativa L. on the moisture, microbe community, enzyme activity, and nutrients in rhizosphere soils of young kiwifruit plants and their growth were investigated. The results show that intercropping V. sativa could effectively enhance soil moisture by 1.39–1.47 folds compared with clean tillage. Moreover, intercropping V. sativa could significantly (p < 0.01) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Although the most well-characterized intercropped systems are those of legume cereal, other systems have been documented as intercropping with rapeseed ( Brassica napus L.), which require higher levels of N fertilizers [ 73 ]. Additionally, the use of V. sativa in kiwifruit orchards increases the microbial community, moisture, and nutrients in the soil, activating plant growth [ 74 ].…”
Section: Environmental Benefitsmentioning
confidence: 99%
“…Although the most well-characterized intercropped systems are those of legume cereal, other systems have been documented as intercropping with rapeseed ( Brassica napus L.), which require higher levels of N fertilizers [ 73 ]. Additionally, the use of V. sativa in kiwifruit orchards increases the microbial community, moisture, and nutrients in the soil, activating plant growth [ 74 ].…”
Section: Environmental Benefitsmentioning
confidence: 99%
“…Multiple studies have demonstrated that kiwifruit can be successfully grown in intercropping systems combined with a variety of crops, such as Amorphophallus konjac, Trifolium repens, Lupin spp., Vulpia myuros, Astragalus spp. (Milk vetch), Lolium perenne L., Vicia sativa L., Reineckea carnea, etc [13][14][15]. In particular, intercropping with Vicia sativa L. and Reineckea carnea has been shown to signi cantly improve the moisture content, microbial community, enzyme activity, and nutrient levels in the rhizosphere soils of kiwifruit plants, enhancing the yield and quality of kiwifruits.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, vetch (Vicia sativa L.) is a very well adapted to Mediterranean conditions forage crop, usually used as an intercrop [19]. Its use is highly recommended, not only due to its high yield and protein content, but also because of its many and well-known effects of improving soil moisture, nutrient content, microbial community [20] and the overall crop sustainability [21].…”
Section: Introductionmentioning
confidence: 99%